UTILIZATION OF GARLIC WITH AND WITHOUT ADDITION OF ENZYMES ON BLACK-CAPPED LORY (LORIUS LORY LINNAEUS, 1758) IN CAPTIVE BREEDING - Sari, Andri Permata; Nugroho, Herjuno Ari; Maharani, Sinta (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTPhytogenic feed additives are plant-derived product such as herbs, spices, and essential oils used in animal feed to improve their performances and health. Garlic (Allium sativum) is well-known as a spice and herbal medicine. Garlic possesses antimicrobial activity and increase nutrient digestibility in animal. The objectives of this study were to compare the effect of supplementing garlic, exogenous enzyme and combination of both on Black-capped Lory (Lorius lory) in digestibility and bacterial count on excreta. Five Black-capped Lory were used in the study and fed with control diet (K1), control diet supplemented with garlic powder (K2), control diet supplemented with Allzyme SSF (K3), and control diet supplemented with both garlic powder and Allzyme SSF (K4). Variables observed include feed consumption, Apparent Metabolizable Energy (AME) value and bacterial count in excreta. Adding enzyme to the diet increased AME compared to control. AME value of K1 was 3,579 kcal/kg, meanwhile AME value of diet K3 and K4 were 3,690 kcal/kg and 3,619 kcal/kg respectively. Adding garlic to the diet did not give significant improvement to AME value. The highest inhibition of bacterial population was in K2 mash. Combination of allzyme and garlic addition showed decreased in bacterial number.Keywords: Allzyme SSF, AME value, bacterial population, black-capped Lory, garlic